Performance analysis of a solar-driven heat engine with external irreversibilities under maximum power and power density condition - Koyun, A (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Thermodynamic optimizations based on the maximum power and maximum power density criteria have been performed for a solar-driven heat engine with external irreversibilities. In the analysis, it is assumed that the heat transfer from the hot reservoir is to be in the radiation mode and the heat transfer to the cold reservoir is to be in the convection mode. The power and power density functions have been derived, and maximization of these functions has been performed for various design parameters. The obtained results for the maximum power and power density conditions have been compared. (C) 2003 Published by Elsevier Ltd.
Keywords: solar driven; power density; finite time thermodynamics; thermodynamics optimization; EFFICIENCY; Thermodynamics; Energy & Fuels; Mechanics